2010
DOI: 10.1063/1.3374688
|View full text |Cite
|
Sign up to set email alerts
|

Ion dose, energy, and species dependencies of strain relaxation of SiGe buffer layers fabricated by ion implantation technique

Abstract: We systematically studied on ion dose, energy, and species dependencies of strain relaxation ratios for SiGe buffer layers fabricated by ion implantation technique where the epitaxial growth of SiGe layers was carried out on Si or Ar ion preimplanted Si substrates. For Si+ implantation, we found that there was an optimal ion-implantation condition to effectively enhance strain relaxation of the SiGe layers, that is, relaxation ratios increased with the ion dose but reduced remarkably when it exceeded a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In particular, threading dislocations (TDs) emerging on the surface can drastically decrease the top layer quality, for example, by affecting the carrier mobility and lifetime in devices 6. Several techniques have been proposed for reducing the TD density, such as annealing steps,7 aspect‐ratio‐trapping (ART)8 and selective area depositions (SAD),9 or growth of buffer layers localizing plastic relaxation, such as virtual graded layers,10 low temperature silicon buffers,11 compliant substrates,12 two‐temperature epilayers13 and ion implanted substrates 14. TD densities as low as few 10 6 cm −2 for micrometer thick Ge layers have been obtained 15.…”
mentioning
confidence: 99%
“…In particular, threading dislocations (TDs) emerging on the surface can drastically decrease the top layer quality, for example, by affecting the carrier mobility and lifetime in devices 6. Several techniques have been proposed for reducing the TD density, such as annealing steps,7 aspect‐ratio‐trapping (ART)8 and selective area depositions (SAD),9 or growth of buffer layers localizing plastic relaxation, such as virtual graded layers,10 low temperature silicon buffers,11 compliant substrates,12 two‐temperature epilayers13 and ion implanted substrates 14. TD densities as low as few 10 6 cm −2 for micrometer thick Ge layers have been obtained 15.…”
mentioning
confidence: 99%
“…Ion implantation is known to be one of the useful tools for the fabrication of relaxed SiGe layers. [10][11][12][13][14][15] When a SiGe layer is grown on an ion-implanted Si substrate, the strain relaxation of the overgrown SiGe layer is largely enhanced because ion-implantation-induced defects in the Si substrate act as effective misfit dislocation nucleation sources. Recently, we have shown that the degree of strain relaxation of SiGe layers can be locally controlled by means of selective ion implantation.…”
mentioning
confidence: 99%
“…In this method, the thin-film relaxed SiGe layers can be fabricated at low temperature owing to defects generated by annealing after ion implantation, which act as dislocation nucleation sources and enhance strain relaxation of the overgrown SiGe layers. [20][21][22][23][24][25] The relaxation ratio in the SiGe layers monotonically increases by increasing the Ar ion dose, and the SiGe layers are largely relaxed on the Ar ion implanted Si substrates with a dose of 1 × 10 15 cm −2 . 22,24) In addition, void-related defects, which are formed around the projected range of the ion implantation, are found to contribute to the strain relaxation of the SiGe layer significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] The relaxation ratio in the SiGe layers monotonically increases by increasing the Ar ion dose, and the SiGe layers are largely relaxed on the Ar ion implanted Si substrates with a dose of 1 × 10 15 cm −2 . 22,24) In addition, void-related defects, which are formed around the projected range of the ion implantation, are found to contribute to the strain relaxation of the SiGe layer significantly. It is therefore thought that the relaxed Si 1−x C x layers with thin thickness can be fabricated on Si substrates at low temperature by utilizing the Ar ion implantation technique.…”
Section: Introductionmentioning
confidence: 99%